Statius' Silvae and the poetics of Empire - Newlands, Carole Elizabeth (Cambridge University Press, 2002)
"Statius' Silvae, written late in the reign of Domitian (AD 81-96), are a new kind of poetry that confronts the challenge of imperial majesty or private wealth by new poetic strategies and forms. As poems of praise, they delight in poetic excess whether they honour the emperor or the poet's friends. Yet extravagant speech is also capacious speech. It functions as a strategy for conveying the wealth and grandeur of villas, statues and precious works of art, as well as the complex emotions aroused by the material and political culture of empire. The Silvae are the product of a divided, self-fashioning voice: Statius was born in Naples of non-aristocratic parents, and his position as outsider to the culture he celebrates gives him a unique perspective on it